Leadership frames of level coordinators and organizational climate as perceived by nursing faculty - Bitera, Ma. Xenia Z.
Leadership has a great impact among the followers in an organization. How the followers perceive the leadership and its organizational climate influence the achievement of the organizational goal. -- This study aimed to determine the Level Coordinators' leadership frames and the organizational climate as perceived by the nursing faculty members in a university-based College of Nursing. It further aimed to explore possible relationship between leadership frames and organizational climate at a university-based College of Nursing during the academic year 2009-2010. --The descriptive correlational research design was used in this study. The population of the study constituted one-hundred ten (110) nursing faculty members of which ten (10) nursing faculty were excluded during the pretesting of the instruments. The sample consisted of ninety-three (93) nursing faculty members, which was ninety-three percent (93%) of the population frame. -- Two standardized questionnaires, with the permission of the authors, were utilized to measure the variables under study: 1) Bolman and Deal's Leadership Orientations Instrument (Other) for the perception among faculty members of the leadership frames used by their Level Coordinators, and (2) Borrevik's Organizational Climate Description Questionnaire-Higher Education for the perception of organizational climate among the nursing faculty members. -- The result of the study revealed that Level Coordinators were perceived as demonstrating all the leadership frames as "sometimes". They were assessed as manifesting most in political frames, more in human relations, followed by structural frames, and least in symbolic frames. On the other hand, organizational climate in the College of Nursing was perceived as half-open, and half-close and "occurring occasionally". It was perceived most as having intimacy among the nursing faculty (open climate), more in production emphasis by the Level Coordinators (close climate) followed by consideration by the Level Coordinators (open climate), and least in disengagement among nursing faculty (close climate). -- Moreover, leadership frames and organizational climate indicated a very high and very significant relationship. Finally, all leadership frames, with the exception of symbolic frames were strong predictor of organizational climate of consideration, intimacy, and production emphasis, except disengagement. -- In the light of the above finding, the following recommendations were made: Conduct leadership trainings and seminars for the Level Coordinators to introduce leadership frames and use them as reference on creating innovations and managing resources. Conduct nursing faculty development to introduce organizational climate and its components to identify and to develop behavior that open climate creates. Human Resources Department, to create programs and activities to foster an open climate in the university. Conduct study among sister schools of this university-based College of Nursing to have a data-base of their leadership frames of Level Coordinators and the organizational climate. Establish criteria for hiring/appointing Level Coordinators, emphasizing critical leadership factors or the behavior of a Level Coordinator